(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
This study moved from the initial observation that the process of implementation and determination of mutations of civil servants in the local government of North Halmahera Regency is less transparent. Thus, the research in addition to answering the problems related to transparency of civil servant mutations, also aims to know the application of the principle of transparency in the implementation of employee mutations at the Regional Personnel Agency (BKD) of North Halmahera Regency. This research applies descriptive method with qualitative approach, informant is determined based on level of understanding to research problem as many as 12 people consisting of element BKD, some related SKPD, Member DPRD related commission and press. Methods of data collection consist of observation, documentation and interview. Processing and data analysis is done from the collection stage to the data verifikasi stage by applying interactive techniques. The results showed that (1). Information relating to the process of formulating and implementing public policies, including information on civil servant mutations, is sufficient, accessible, accessible and timely, but information is categorized as "confidential", including information on the process and determination of civil servants to be transferred. (2). Transparency of information may increase the knowledge and insight of the community about the process, procedures, requirements and reasons for the transfer of civil servants, there are several considerations of civil servant’s mutation among others is the need for civil servants to fill vacant places / positions. Given the transparency of civil servant transfers, at least a slight increase in public confidence in the government. The level of public trust to the government due to the increased satisfaction is significant. Thus it can be concluded that the existence of transparency of information in terms of civil servant’s mutations also affect the increased knowledge, insight, trust and community participation in regional development. Participation in question has to do with reports for civil servants need to be transferred (critical Participation) to provide information to the government about the existence of deviation by civil servants that need to be transferred. It is recommended that the process and procedure of the PNS mutation should be done transparently, openly and based on mapping the needs of employees by SKPD or at the request of SKPD and not because of other factors beyond that. A strategic partner organization that is neutral for local government to oversee the process of employee reform is necessary to prevent the KKN practices in the process. Keywords: Transparency, Employee Mutation